Managing deep sea mining revenues for the public good- ensuring transparency and distribution equity. (September 2018) - Ovesen, Vidar; Hackett, Ron; Burns, Lee; Mullins, Peter; Roger, Scott
Abstract: This paper is intended to provide an overview of key issues in the financial management of revenues and wealth associated with development of deep sea minerals. Setting up frameworks for DSM revenue management is a complex task. The paper should help the authorities identify what they need to do to maximize the benefits of DSM wealth for their citizens. The paper is the product of a close collaboration between the Geoscience Division (GSD) of the Pacific Community (SPC), and those of the Pacific Financial Technical Assistance Centre (PFTAC) of the International Monetary Fund (IMF). It was produced with the financial assistance of the European Union and the International Monetary Fund. Highlights: The exploitation of deep sea mineral (DSM) deposits in the Pacific has the potential to generate new, and possibly substantial, revenues for countries in the region. Poorly managed, such wealth may not only be wasted, but also has the potential to cause great economic and social harm.